Pelatihan Pemanfaatan Daun Beluntas (Pluchea indica) Sebagai Produk Kesehatan di Sidomekar Semboro Kabupaten Jember - Puspaningtyas, Ayik Rosita; Sary, Indah Purnama (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The many kinds of health benefits of beluntas (Pluchea indica) are already known, but are still limited for vegetables, even though its essential oil is very high. Essential oils, based on research, can be used as an antibacterial and an inhibitor of viruses. Therefore, we conducted counseling and training on the utilization of Beluntas leaf essential oil through isolation to be developed into health products in the Babatan Sidomekar community, Semboro, Jember. The Covid 19 virus pandemic in Indonesia has had an economic impact on small communities. One way to do this is to provide new knowledge and technology by producing products that can be used to increase income and preventive against COVID-19. Presentation products are more modern, have high selling value, and are more durable, which will be easily accepted by the market. The stages of implementing the activity were socialization in the Babatan Sidomekar community, Semboro, Jember, which was carried out well from August to November 2022, and the community was very enthusiastic about receiving counseling and training in making hand sanitizer and antiseptic soap products from the essential oil of beluntas leaf